Animals as a medium for criticism and reflection: Zoo-semiotics in the short story “Sesat Pikir Para Binatang” by Triyanto Triwikromo - Fadhilla, Indah; Pasaribu, Rouli Esther (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This research analyzes the short story “Sesat Pikir Para Binatang” by Triyanto Triwikromo using a zoo-semiotic approach from Thomas Albert Sebeok, who studies the role of animals as signs in human symbolic communication. The animals in this short story not only function as characters in the story, but also as a reflection of human identity to convey criticism of anthropocentrism and a reflection of human morality. By using zoo-semiotic theory, this research reveals that e zoo narrative in the short story is an allegory of human life, which is full of hierarchy, contradiction, and manipulation. Animal characteristics are seen as ethograms that can be interpreted symbolically. The symbolism of animals, such as elephants, worms, and other creatures, reflects the weaknesses of humans who often project their nature and internal conflicts onto animals. This research contributes to the study of contemporary Indonesian literature and expands the application of zoo-semiotics in literary studies, especially in exploring the relationship between humans and animals. Keywords: zoo-semiotics; ethogram; animal symbolism; anthropocentric; hierarchy; morality